GAMBARAN POLA MAKAN DAN KEJADIAN OBESITAS PADA MASYARAKAT SUKU GAYO DI DESA TITI PASIR KECAMATAN SEMADAM KABUPATEN ACEH TENGGARA TAHUN 2017 - Nurul Mawaddah; Jumirah .; Ernawati Nasution (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2017)
Nutrition problem has been the main of health problem in Indonesia. In the globalization era, Indonesia faces a double nutrition problem, they are the problem of malnutrition and over nutritio. As a developing country, cases of malnutrition have long existed in Indonesia, but with diet changing, economic progress, and lack of nutritional knowledge has made the increasing number of overnutrition in Indonesia. one of the more nutritional problems is obesity. Based on the Aceh Province Health Profile 2015, the percentage of adult male population is obese as much as 17%, while the percentage of adult female population who are obese as much as 20%. The results of preliminary survey showed that from 66 adults in Titi Pasir Village, Semadam Subdistrict, there were 15.15% of people who were overweight, 74.24% were obese, and 10.60% were normal. This is related to eating habits in the Gayo ethnic population in Titi Pasir Village with a diet high in carbohydrate and fat consumption and consumption of foods that are not diverse. The purpose of this study was to know the description of eating patterns and the incidence of obesity of Gayo ethnic in Titi Pasir Village Semadam District Southeast Aceh Year 2017. Type of research used is descriptive with cross sectional research design. The population in this study were Gayo ethnic adult population aged 19-44 years as many as 863 people with a sample of 90 people. The results showed that the diet of Gayo ethnic population based on food type 87.8% was not diverse, edequacy of energy in more category 75,6%, adequacy of carbohydrate in more category 57,8%, adequacy of protein in more category 82,2%, and adequacy of fat in more category 67,8%. Obesity status in Gayo ethnic population 67,8% with obesity and 32,2% without obesity. It is hoped that the Health Office of Southeast Aceh Regency, Sub-district Health Center, and health workers to do counseling about obesity problem and healthy and balanced diet with the aim of increasing knowledge and awareness about the impact of obesity that will cause degenerative diseases so that the prevalence of obesity decreases and improves public health status. Key Words: Eating Patern, Obesity, Gayo Ethnic.